Аtmospheric wind flow around the mountain landscape in the vicinity of Danang airport and flight safety issues - Vyshinsky, V. V.; Zoan, K. T. (Nauchnyĭ vestnik MGTU GA (Online), 2021)
Wind boundary layer flow over the mountain landscape and large structures located around runways (RWs) creates coherent vortex structures (CVSs) that can cross a glideslope and airspace in the vicinity of an airport. The aircraft, encountering a vortex structure, experiences significant changes of the aerodynamic forces and moments, what is especially hazardous due to proximity to terrain. From a mathematical point of view, the solution of this problem presents a challenge due to extremely large space – time scale of the phenomenon, the lack of relevant atmospheric models, as well as comprehensive initial – boundary conditions in numerical modeling. In this paper, a composite solution is constructed: the CVSs area generation is computed in sufficient details within the framework of the grid method. Based on the data obtained in the approximation of analytical functions, an initial vortex structure is formed, the evolution and stochastics of which are modeled within the potential approximation by means of Rankine vortices. The evaluation of the forces and moments increment from the impact of vortex structures on the aircraft was carried out by the panel method using the engineering approach. As an example, the CVSs, resulting from wind flow around the mountainous area of the Son Tra Peninsula, that is located short of RWs 35R-17L and 35L-17R of Da Nang airport, are investigated. To improve the computational grids quality and verify the method of solving the boundary value problem for the Reynolds-averaged Navier-Stokes equations, we used the criteria based on the principle of maximum pressure, requiring Q-parameter positivity property in the vortices cores and flow separation regions. A CVS related aviation event, involving a passenger aircraft MC-21, is studied. The aircraft, after takeoff from RW 35R-17L setting the course close to the direction of the vortex wind structure axis from the Son Tra Peninsula, encountered the mountainous area CVS.